Drug-eluting Bead-Transcatheter Arterial Chemoembolization for Advanced Hepatocellular Carcinoma Refractory to Conventional Lipiodol-based Transcatheter Arterial Chemoembolization - Kobayashi, Saito (J Hepatocell Carcinoma, 2020)
PURPOSE: To evaluate the potential of drug-eluting bead (DEB)-transcatheter arterial chemoembolization (TACE) as a treatment option for patients with refractory to conventional lipiodol-based TACE (c-TACE) especially with decreased liver function. PATIENTS AND METHODS: We retrospectively evaluated the treatment results of DEB-TACE for 89 HCC nodules in 27 patients with c-TACE refractory according to liver function. RESULTS: Although overall survival was significantly better in Child–Pugh A patients than in Child–Pugh B patients (median survival time, MST: 561 vs 347 days, p=0.031), progression-free survival was almost similar in both patients between Child–Pugh A and B (MST: 79 vs 87 days, p=0.534). Regarding antitumor response, the objective response rate (ORR) and disease-control rate (DCR) were 5.3/12.5% and 52.7/87.5% in Child–Pugh A/B, respectively. In each 89 HCC nodules, ORR and DCR were almost similar between Child–Pugh A and B (ORR, 20.3 vs 13.3%; DCR, 77.0 vs 73.3%, respectively). Adverse events of DEB-TACE were well-tolerated, and liver function was reserved during DEB-TACE procedures. CONCLUSION: DEB-TACE could be a therapeutic option for advanced HCC patients with c-TACE refractory and decreased liver function.